RECONCILIATION FROM THE TOP DOWN? GOVERNMENT INSTITUTIONS IN SOUTH AFRICA, RWANDA AND BURUNDI (The Strategic Review for Southern Africa, 2020)
National reconciliation has increasingly become an integral part of post-conflict recovery processes in Africa. What national reconciliation means, how it differs from interpersonal reconciliation and to what extent governments can facilitate reconciliation at all remains under debate. This article examines government institutions intended to facilitate national reconciliation processes in South Africa, Rwanda and Burundi. Rather than normatively prescribing what governments should be doing, this article seeks to examine what governments are doing as a starting point to understanding what national reconciliation is.